Nicotinamide Mononucleotide, an NAD(+) Precursor, Rescues Age-Associated Susceptibility to AKI in a Sirtuin 1–Dependent Manner - Guan, Yi (J Am Soc Nephrol, 2017)
The rapid growth of an aging population creates challenges regarding age-related diseases, including AKI, for which both the prevalence and death rate increase with age. The molecular mechanism by which the aged kidney becomes more susceptible to acute injury has not been completely elucidated. In this study, we found that, compared with the kidneys of 3-month-old mice, the kidneys of 20-month-old mice expressed reduced levels of the renal protective molecule sirtuin 1 (SIRT1) and its cofactor NAD(+). Supplementation with nicotinamide mononucleotide (NMN), an NAD(+) precursor, restored renal SIRT1 activity and NAD(+) content in 20-month-old mice and further increased both in 3-month-old mice. Moreover, supplementation with NMN significantly protected mice in both age groups from cisplatin-induced AKI. SIRT1 deficiency blunted the protective effect of NMN, and microarray data revealed that c-Jun N-terminal kinase (JNK) signaling activation associated with renal injury in SIRT1 heterozygotes. In vitro, SIRT1 attenuated the stress response by modulating the JNK signaling pathway, probably via the deacetylation of a JNK phosphatase, DUSP16. Taken together, our findings reveal SIRT1 as a crucial mediator in the renal aging process. Furthermore, manipulation of SIRT1 activity by NMN seems to be a potential pharmaceutical intervention for AKI that could contribute to the precise treatment of aged patients with AKI.